2022
DOI: 10.1136/bmjpo-2021-001348
|View full text |Cite
|
Sign up to set email alerts
|

Parenting a newborn baby during the COVID-19 pandemic: a qualitative survey

Abstract: ObjectiveThe COVID-19 pandemic caused long periods of lockdown, social isolation and intense challenges for parents. This study examines parenting in an infant cohort born at the pandemic onset.MethodsThe CORAL study is a prospective longitudinal observational study looking at allergy, immune function and neurodevelopmental outcome in babies born between March and May 2020. Demographic information was collected, babies were reviewed at 6-monthly intervals, and serology for COVID-19 infection was recorded. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…These findings may also be linked to one or both parents (due to home working) and siblings (out of school and day care) being in close proximity and anticipating babies’ needs before the need for pointing arises. There was also a reduction in the babies’ ability to wave bye-bye which is likely due to a reduction in number of opportunities where babies can learn to wave bye-bye due to reduced social contacts 1. However, it is worth noting that the overall relative risk reductions in this study are small and it is hoped that these infants will catch up with their pre-pandemic peers quickly once restrictions are lifted.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…These findings may also be linked to one or both parents (due to home working) and siblings (out of school and day care) being in close proximity and anticipating babies’ needs before the need for pointing arises. There was also a reduction in the babies’ ability to wave bye-bye which is likely due to a reduction in number of opportunities where babies can learn to wave bye-bye due to reduced social contacts 1. However, it is worth noting that the overall relative risk reductions in this study are small and it is hoped that these infants will catch up with their pre-pandemic peers quickly once restrictions are lifted.…”
Section: Discussionmentioning
confidence: 75%
“…Stringent lockdown, used to control the COVID-19 pandemic, has led to babies and their families spending more time at home than babies from previous years. We recently demonstrated that families of babies in the CORAL cohort had a median of one social contact outside the home at birth, increasing to four when the babies reached 6 months of age 1. This may have impacted on parents’ experience of raising a child during the pandemic, as many parents noted that they were isolated 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations